2005
DOI: 10.1111/j.1460-9568.2005.04440.x
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral amygdala glutamatergic activation enhances taste aversion through NMDA receptor activation in the insular cortex

Abstract: In conditioned taste aversion (CTA), a subject learns to associate a novel taste with visceral malaise. Brainstem, limbic and neocortical structures have been implicated in CTA memory formation. Nevertheless, the role of interactions between forebrain structures during these processes is still unknown. The present experiment was aimed at investigating the possible interaction between the basolateral nucleus of the amygdala (BLA) and the insular cortex (IC) during CTA memory formation. Injection of a low dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 60 publications
4
54
0
2
Order By: Relevance
“…Lamprecht et al (35) also showed that inhibition of cAMP response element-binding protein (CREB), one of the regulatory transcriptional factors for c-fos gene expression, in the AMY with in vivo AS-ODN technology disrupted the retention, but not the acquisition, of CTA. In line with these results, Bermudez-Rattoni and colleagues (36,37) have suggested that positive interaction between the basolateral AMY-IC enhances the strength of long-term CTA memory.…”
Section: Discussionsupporting
confidence: 67%
“…Lamprecht et al (35) also showed that inhibition of cAMP response element-binding protein (CREB), one of the regulatory transcriptional factors for c-fos gene expression, in the AMY with in vivo AS-ODN technology disrupted the retention, but not the acquisition, of CTA. In line with these results, Bermudez-Rattoni and colleagues (36,37) have suggested that positive interaction between the basolateral AMY-IC enhances the strength of long-term CTA memory.…”
Section: Discussionsupporting
confidence: 67%
“…The ''hit rate'' for MePD microinjections reflects the rigorous including criteria and the small size of this brain subnucleus (see also King et al, 1999;Grundmann et al, 2005). The doses of glutamate were adapted from previous reports, that is, the lowest dose of glutamate is close to the physiological values obtained by brain microdialysis in various amygdaloid nuclei and the highest dose is a pharmacological one (Fillenz, 1995;Kaura et al, 1995;Ferreira et al, 2005). Microinjections in the MePD were done while gently restraining the rat, lasted for 1 min and the needle remained inside the cannula for an additional minute to avoid reflux (de Castilhos et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…An animal is classically judged as aversive on the basis of its decrease of consumption measured during the entire session (Ferreira et al, 2005;Chapuis et al, 2007); however, our experimental design allowed us to distinguish, within aversive groups, two behavioral responses across the different trials of the same test session. As illustrated by the examples of licking pattern (Fig.…”
Section: Coa Acquisitionmentioning
confidence: 99%